User-Generated Content and Bias in News Media - Yildirim, Pinar; Gal-Or, Esther; Geylani, Tansev (Management Science, 2013)
In this study, we investigate newspapers' decision to expand their product lines by adding online editions that incorporate user-generated content. We demonstrate that such product line extensions mitigate the extent of slanting in print media. The results also show that as the extent of discretion of users to generate online content increases, print versions of newspapers become more polarized. Furthermore, adding online editions results in reduced profits for newspapers as the additional product variants increase the intensity of competition in the market and the discretion awarded to users limits the ability of newspapers to extract rents from consumers. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2013.1746 . This paper was accepted by J. Miguel Villas-Boas, marketing.